Transforming welfare - incentives, localisation and non-discrimination - Kristian Niemietz (Institute of Economic Affairs (IEA), 2010)
Radical solutions need to be sought to get people off welfare and back into work. In the thirty-second IEA Discussion Paper, Poverty Research Fellow Kristian Niemietz puts forward solutions which would substantially simplify the welfare system, put in place better incentives to encourage work and discourage welfare dependency.They tackle the full extent of the system from middle class benefits to those who are unemployed, those working part-time and those on low full-time incomes. If adopted this system would see less money being spent on bureaucracy, more people in work and people keeping more of their own money in the first place.
Keywords: 330